Exercise-Induced Epigenetic Modifications: Implications for Healthy Aging - Yang, Qi; Hu, Yue; Zhang, Bing; Hong, Weihao (International Journal of Sports Medicine, 2025)
Aging is a complex biological process driven by the dynamic interplay among genetic, environmental, and lifestyle factors. Advances in epigenetics have significantly deepened our understanding of the molecular mechanisms underlying aging, underscoring the critical roles of reversible modifications such as DNA methylation, histone modifications, and noncoding RNA regulation. Emerging evidence suggests that exercise is a potent modulator of these epigenetic processes, capable of reshaping the epigenetic landscape to restore cellular homeostasis, modulate gene expression, and enhance physiological resilience. This review systematically synthesizes current knowledge on how exercise modulates epigenetic mechanisms implicated in aging and delineates the distinct epigenetic adaptations induced by variations in exercise modality, intensity, and duration. By integrating these molecular insights, this review provides a comprehensive mechanistic framework linking exercise-induced epigenetic remodeling to healthy aging, and underscores exercise as a promising intervention to counteract aging-related functional decline and disease progression.
Keywords: exercise; aging; epigenetics; DNA methylation; histone modification; non-coding RNA